2020
DOI: 10.1002/cncy.22362
|View full text |Cite
|
Sign up to set email alerts
|

ThyroSeq v3 for Bethesda III and IV: An institutional experience

Abstract: Background The ThyroSeq v3 genomic classifier is a commercial molecular test that examines a wide spectrum of genomic alterations in a thyroid fine‐needle aspiration (FNA) sample and reports test results as either negative or positive. The authors report their institutional experience with ThyroSeq v3. Methods Thyroid FNA specimens diagnosed as either atypia of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS) (Bethesda category III [Bethesda III] according to The Bethesda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 11 publications
(23 reference statements)
4
52
0
Order By: Relevance
“…28 Accordingly, THADA fusion cases were present in both 3A and 3C, with one eventually diagnosed as NIFTP and the other diagnosed as follicular variant of PTC. Although few such cases were present in our cohort, Desai et al 23 noted that 10 of 11 patients with THADA fusions, 1 of 4 with PTEN mutations, and 1 of 1 with a TERT mutation had a malignant diagnosis. In the literature review conducted by Goldner et al, 12 malignancy was present in 13 of 14 patients with THADA fusions, in 7 of 8 with TERT mutations, and in 0 of 2 with PTEN mutations.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…28 Accordingly, THADA fusion cases were present in both 3A and 3C, with one eventually diagnosed as NIFTP and the other diagnosed as follicular variant of PTC. Although few such cases were present in our cohort, Desai et al 23 noted that 10 of 11 patients with THADA fusions, 1 of 4 with PTEN mutations, and 1 of 1 with a TERT mutation had a malignant diagnosis. In the literature review conducted by Goldner et al, 12 malignancy was present in 13 of 14 patients with THADA fusions, in 7 of 8 with TERT mutations, and in 0 of 2 with PTEN mutations.…”
Section: Discussionmentioning
confidence: 58%
“…These were associated with follicular adenoma, follicular carcinoma, and, less likely, PTC. Similarly, Desai et al 23 noted that RAS mutations were the most common alterations in their cohort as well, and they were also associated with a lower risk of malignancy. As in our study, Bellevicine et al 22 found RAS mutations with all types of atypia.…”
Section: Discussionmentioning
confidence: 75%
“…21,[38][39][40] Furthermore, the likelihood that a specimen will fall into an indeterminate TBS category differs, depending on its morphologic features, particularly architectural pattern and nuclear atypia. [41][42][43][44][45][46][47][48][49] In other words, although they successfully account for differences in the overall malignancy rate, QA metrics such as the NGA rate and the III:VI ratio, which are limited to the characteristics of a single TBS category, fail to account for differences in the distribution of types of malignancy (ie, follicular carcinoma, follicular variant of PTCA, classical variant of PTCA, etc) across different populations. To account for those differences, the calculation of additional, potentially onerous QA metrics across all TBS categories would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, research has also shown that certain morphologic subtypes correlate strongly with the presence of specific genetic alterations 21,38‐40 . Furthermore, the likelihood that a specimen will fall into an indeterminate TBS category differs, depending on its morphologic features, particularly architectural pattern and nuclear atypia 41‐49 . In other words, although they successfully account for differences in the overall malignancy rate, QA metrics such as the NGA rate and the III:VI ratio, which are limited to the characteristics of a single TBS category, fail to account for differences in the distribution of types of malignancy (ie, follicular carcinoma, follicular variant of PTCA, classical variant of PTCA, etc) across different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the recommended usual management for AUS/FLUS is repeat FNA, molecular testing, or lobectomy in the 2nd ed. TBSRTC, compatible with both TIR3A and TIR3B, in spite of propounding ROM of Category III, TBSRTC, 2nd ed., is consonant with TIR3B, ICCRTC 5,6 . We recently emphasized whether it is essential to maintain Category III, TBSRTC as a unique and indivisible category, per se, among indeterminate cytology of thyroid nodules or not, published in Volume 67, Revista da Associação Médica Brasileira 7 .…”
mentioning
confidence: 97%